Worldwide burden of cervical cancer in 2008. - M. Arbyn; Castellsagué, X; de Sanjosé, S; Bruni, L; Saraiya, M; Bray, F; Ferlay, J (Ann Oncol, 2011)
BACKGROUND: The knowledge that persistent human papillomavirus infection is the main cause of cervical cancer has resulted in the development of assays that detect nucleic acids of the virus and prophylactic vaccines. Up-to-date and reliable data are needed to assess impact of existing preventive measures and to define priorities for the future. MATERIALS AND METHODS: Best estimates on cervical cancer incidence and mortality are presented using recently compiled data from cancer and mortality registries for the year 2008. RESULTS: There were an estimated 530,000 cases of cervical cancer and 275,000 deaths from the disease in 2008. It is the third most common female cancer ranking after breast (1.38 million cases) and colorectal cancer (0.57 million cases). The incidence of cervical cancer varies widely among countries with world age-standardised rates ranging from <1 to >50 per 100,000. Cervical cancer is the leading cause of cancer-related death among women in Eastern, Western and Middle Africa; Central America; South-Central Asia and Melanesia. The highest incidence rate is observed in Guinea, with ∼6.5% of women developing cervical cancer before the age of 75 years. India is the country with the highest disease frequency with 134,000 cases and 73 000 deaths. Cervical cancer, more than the other major cancers, affects women <45 years. CONCLUSIONS: In spite of effective screening methods, cervical cancer continues to be a major public health problem. New methodologies of cervical cancer prevention should be made available and accessible for women of all countries through well-organised programmes.
Keywords: Alphapapillomavirus; Female; Humans; incidence; Papillomavirus Infections; prevalence; Uterine Cervical Neoplasms